2020
DOI: 10.1136/sextrans-2019-054386
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide and fluoroquinolone resistance ofMycoplasma genitaliumin southern Spain, 2018–2019

Abstract: ObjectivesIn recent years, resistance in Mycoplasma genitalium (MG) to first-line (azithromycin) and second-line (moxifloxacin) treatment has been increasingly reported worldwide, however, no data regarding the south of Spain are available.MethodsTo determine resistance rates, MG-positive samples collected from June 2018 to June 2019 were analysed by sequencing the 23S rRNA and parC genes.ResultsA total of 77 patients (24 men having sex with men (MSM), 30 heterosexual men and 23 women) were included. Resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 10 publications
6
16
3
1
Order By: Relevance
“…Similar to other studies, the most common change found in the QRDRs in this study was Pro62Ser (C184T) [25]. However, this mutation was not specific to G3 (P=0.459) (Table 2) and the A2059G SNP was positively correlated with the presence of proline instead of serine in parC62 (P=0.037) (Table 4).…”
supporting
confidence: 88%
“…Similar to other studies, the most common change found in the QRDRs in this study was Pro62Ser (C184T) [25]. However, this mutation was not specific to G3 (P=0.459) (Table 2) and the A2059G SNP was positively correlated with the presence of proline instead of serine in parC62 (P=0.037) (Table 4).…”
supporting
confidence: 88%
“…The 23S rRNA mutation is associated with macrolide resistance [61]. We found that SNPs in region V of the 23S rRNA gene were observed in 101 (66.4%) samples from male and female patients with M. genitalium-positive infection in 2016-2018.…”
Section: Discussionmentioning
confidence: 87%
“…However, this review included few studies of MSM. MSM appear significantly more likely to harbour macrolide-resistant MG infections than other populations (Couldwell et al, 2018;McIver et al, 2019;Bradley et al, 2020;Berçot et al, 2021;De Salazar et al, 2021;De Baetselier et al, 2022). In Malta, which has been lacking any MG AMR data hitherto, MRAMs, QRAMs and dual resistance in MSM were detected at prevalence of 68.1, 29.0 and 20.7%, respectively.…”
Section: Discussionmentioning
confidence: 96%